Principle of Solidarity and its Impact on the Harmonization of Asylum Law in the European Union - Riševičiūtė, Vita (Teisė, 2025)
Against the backdrop of the migration processes that have been taking place in Europe over the last decade, disagreements over the content of the principle of solidarity have become an increasingly important factor on national political and legal agendas. In this context, it is important to analyze the evolution of the European Union (EU) asylum acquis starting from its very genesis – the Treaty of Amsterdam – to its current stop which appears to be the very recent collection of legal documents adopted by the European Parliament in April 2024 – the so-called New Pact on Migration and Asylum (New Pact). This research was carried out in order to assess the content and role of the principle of solidarity for the Common European Asylum System (CEAS) and the harmonization of the asylum acquis.
Keywords: harmonization; solidarity; burden sharing; Common European Asylum System (CEAS); New Pact on Migration and Asylum